HOTS about Environment and Designing Science Serial Books for Digital Learning in Elementary School - Ilmi Zajuli Ichsan; Santhi Pertiwi; Yudi Hermawan (Postgraduate, University of Mataram, 2022)
Environmental education is one of the important aspects of Higher Order Thinking Skills (HOTS)-based elementary school learning. The use of learning media for e-learning implementation requires HOTS-based evaluation. This study aims to perform analysis related to HOTS and the utilization of e-learning in elementary school (SD). The method used in the research is the descriptive method with a survey as the data collection technique. The research instrument is in the form of a test question to measure HOTS based on Anderson’s taxonomy and Ichsan’s taxonomy. The second instrument employed is a questionnaire containing questions related to learning and various obstacles in e-learning. The research finds that the average HOTS score of elementary school students measured using Anderson’s taxonomy is 2.58; whereas, those measured with Ichsan’s taxonomy is 2.27 for all items. The HOTS measurement results using both taxonomies have some differences and one of them is in the C6 realm (create versus develop). The measurement results using the questionnaire suggest that WhatsApp is the frequently-used learning media (65.97%). Moreover, the most ideal learning duration according to the students is less than 3 hours (67.36%). The utilization of learning media become an important matter in the implementation of e-learning to enhance elementary school students’ HOTS. Serial books are an alternative solution so that students can understand environmental material well. The research concludes that differences in HOTS scores occurred between those measured with Anderson’s taxonomy and Ichsan’s taxonomy. Learning media to be further developed should be HOTS-based